Improvement in Quality of Life with Use of an Unloader Knee Brace in Active Patients with OA: A Prospective Cohort Study - Briggs, Karen K.; Matheny, Lauren M.; Steadman, J. Richard (The Journal of Knee Surgery, 2012)
The purpose of this study was to determine if short form (SF)-12 physical component would increase with unloader brace use. Patient expectations and predictors of significant improvement were determined. Our hypothesis was that patients with unloader braces will have increases in general physical health (SF-12) and function (Western Ontario and McMaster Universities Arthritis Index [WOMAC]). Patients were enrolled in institutional review board-approved prospective cohort study. They completed a self-administered questionnaire (SF-12; WOMAC, Tegner activity scale, expectations) at enrollment, 3 weeks, 6 weeks, and 6 months. In this study, 39 patients, 23 males and 16 females (average age = 61 years [range 44 to 87]), were prescribed an unloader brace. Patients had significant improvement in quality of life (SF-12) (p < 0.05). There was significant improvement in pain, stiffness, and function (WOMAC) (p < 0.05). Patients who reported Tegner of 3 or greater at final follow-up had significantly higher SF-12 physical component (48 vs. 37; p = 0.023). Return to recreational sports was very important in 83% and somewhat important in 17%. Improving ability to walk was very important in 89%. Pain relief was very important in 69%, somewhat important in 17%. Of these, 39% expected most pain to be relieved and 57% expected all pain to be relieved. The most important expectations were to have confidence in knee (97% very important), avoid future knee degeneration (90% very important), and improve ability to maintain general health (93% very important). Patients demonstrated a significant decrease in pain and disability. Patients saw improvement in SF-12 physical component. Braces specifically designed to unload the degenerative compartment of the knee can be an effective treatment to decrease pain and maintain activity level to increase overall physical health.
Keywords: knee; osteoarthritis; quality of life